2017
DOI: 10.1002/cppb.20049
|View full text |Cite
|
Sign up to set email alerts
|

X‐Ray Computed Tomography of Crop Plant Root Systems Grown in Soil

Abstract: Non‐destructive methods to quantify the root system architecture of a plant grown in soil are essential to aid our understanding of the factors that impact plant root development in natural environments. With environmental change threatening our ability to sustain agricultural productivity for an expanding global population, the application of these methods has never before seen such an increase in demand. X‐ray computed tomography (CT) based phenotyping techniques permit the spatio‐temporal quantification of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 16 publications
0
22
0
Order By: Relevance
“…A17 WT or cra2‐11 were grown in sieved (< 2 mm) sandy loam soil uniformly packed to a bulk density of 1.1 mg m −3 in a 68 mm (diameter) × 160 mm (height) cylindrical column made from high density polyethylene (Mairhofer et al , 2017) for 21 d in a Conviron A1000 growth chamber at 22°C, 60% humidity with a 16 h photoperiod. After 14 d or 21 d growth, each column was scanned using a GE v|tome|x M 240 kV X‐ray CT system at the Hounsfield Facility, University of Nottingham (UK).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A17 WT or cra2‐11 were grown in sieved (< 2 mm) sandy loam soil uniformly packed to a bulk density of 1.1 mg m −3 in a 68 mm (diameter) × 160 mm (height) cylindrical column made from high density polyethylene (Mairhofer et al , 2017) for 21 d in a Conviron A1000 growth chamber at 22°C, 60% humidity with a 16 h photoperiod. After 14 d or 21 d growth, each column was scanned using a GE v|tome|x M 240 kV X‐ray CT system at the Hounsfield Facility, University of Nottingham (UK).…”
Section: Methodsmentioning
confidence: 99%
“…Data were reconstructed and subjected to manual root segmentation techniques to digitally separate the roots from the soil. Extracted RSAs were quantified using R ooth software (Mairhofer et al , 2017) for total root length, branch structure and LR angle.…”
Section: Methodsmentioning
confidence: 99%
“…Visualization and quantification of root material in the reconstructed data were preformed using the method of Tracy et al (2012) , employing a combination of the VGStudioMAX v2.2 (Volume Graphics GmbH, Heidelberg, Germany) and RooTrak software ( Mairhofer et al , 2012 ). For the measurement of root angles, a bespoke software tool called RooTh was used ( Mairhofer, et al , 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, additional techniques for identifying and removing false positives are an avenue for future work. In its current form, we found that it was possible to extract the primary root system for quantification using an existing tool [38]. This tool traverses the primary root system from detected tip locations to the seed, and fits smooth polynomial splines to major roots.…”
Section: Discussionmentioning
confidence: 99%